Crashworthiness of Light Cab Commercial Vehicles: A Systematic Review on Frontal Collision Cases - M. H. Johari; K. A. Abu Kassim; Y. Ahmad; S. S. Syed Zainuddin; S. N. N. Syed Muhaimin; M. R. A. Mansor (Journal of the Society of Automotive Engineers Malaysia, 2022)
Light cab commercial vehicles, which are also known as light trucks or technically as N1 category vehicles, are designed to carry loads below the maximum capacity of 3.5 tons. With the aim of maximizing cargo size, the occupant cabin has been pushed to the front as far as possible, thus the vehicle design appears as a “flat head” type. In general, the flat head structure has compromised the crashworthiness of these vehicles in the event of a frontal collision. The purpose of this study is to review the findings of previous studies on the crashworthiness of light cab commercial vehicles in the Asian region and to ascertain the level of driver injuries in a frontal collision. The results of several published studies on the crashworthiness of light cab commercial vehicles were analyzed via a systematic review. Preferred Reporting Items for Systematic Review and Meta- analyses, PRISMA-P guidelines were used to complete the review process. The inclusion criteria included studies of the crashworthiness of light cab commercial vehicles and passenger injuries published between 2000 and 2020 in PubMed, Taylor & Francis, and the ASME Digital Collection. In summary, it was found that four studies (31%) provided information on commercial vehicle driver behavior, seven studies (54%) vaguely described the crashworthiness of light cab commercial vehicles, and only two studies (15%) provided detailed information on the subject matter. The topic of N1 vehicle crashworthiness was found to be unattractive in the current academia, prompting necessary emphasis on the safety issues related to this type of commercial light truck.